Strength Investigation of Main Frame in New ``Track friendly'' Railway Bogie - Stastniak, Pavol; Moravcik, Marian; Smetanka, Lukas; Baran, Peter (Manufacturing Technology Journal, 2018)
The paper deals with the strength conditions assessment of new design of modern railway bogie through FEM analysis. The bogie, which was developed as part of European structural funds project, is characterized mainly by better dynamic properties while driving on the track, higher safety against derailment and lower negative effect on the track (reduction of wear). For analysis of bogie frame, there has been created a substitute simulation model. Results from calculations and prototype tests prove, that investigated design of new construction satisfies strength conditions.
Keywords: Strength Tests; Bogie Frame; Computer Simulation